Estudos da reindução de tolerância à dessecação em plântulas de Handroanthus impetiginosus originadas de sementes de diferentes biomas - Schio, Franciane (2016)
Handroanthus impetiginosus (Mart. Ex DC.) Mattos has wide geographical distribution, and an interesting species to evaluate the re-induction of desiccation tolerance in populations of different biomes seedlings, so were evaluated Mato Grosso State seedlings. Seeds were collected in the cerrado biome, Amazon and Cerrado/transition Amazon region. The seeds prepared for germination were placed in temperature of 30 °C and photoperiod of 12 hours, being taken with protrusion of up to 2 mm radicle and divided into four replicates of 30 individuals each treatment, namely: biome collection and drying time (0, 3, 6, 9, 12, 15, 18 and 21 hours). The seedlings were placed for drying in open boxes gerbox on silica gel in sealed plastic boxes with control of relative humidity of 10%. The water content was measured 3 in 3 hours, removing treatment and putting them back to reembebição in a germination chamber for recovery of the root growth, checking if there survival. Data were submitted to analysis of variance (ANOVA) followed by Tukey test at 5% significance level for comparison of averages. With the survival data and thousand seed weight correlations were performed Pearson with the meteorological variables of each biome. The species showed different levels of survival among biomes, Cerrado seedlings had higher re-induction capacity of desiccation tolerance, while seedlings of the Amazon forest had more mortality.